Storm over Uluru : the greatest hoax of all : a resume of events leading up to the questionable hand-over of Australia's most famous National Park to Aboriginal claimants - English, Peter B., 1916- (Bullsbrook, W.A. : Veritas Publishing, 1986)
Journalistic discussion of role of NT and Federal Governments in Uluru handover; argues Jankuntjatjara tribe is sole traditional owner; uses material of T. Strehlow in discussing mythology.
Keywords: Aboriginal Australians -- Northern Territory -- Ayers Rock -- Land tenure; Land rights - Handbacks; Pitjantjatjara people (C6) (NT SG52-11); Land rights - Claims, disputes, hearings; Yankunytjatjara language (C4) (NT SG52-16); Religion - Totemism; Religion - Rites - Ceremonial objects; Councils - Land Councils; Yankunytjatjara people (C4) (NT SG52-16); Kata Tjuta / Olgas (South Central NT SG52-08); Mutidjula / Maggie Springs (South Central NT SG52-08); Uluru / Ayers Rock (South Central NT SG52-08)